Aromatic C–H bond functionalization through organocatalyzed asymmetric intermolecular aza-Friedel–Crafts reaction: a recent update - Biswas, Anup (Beilstein Journal of Organic Chemistry, 2023)
The aza-Friedel–Crafts reaction allows an efficient coupling of electron-rich aromatic systems with imines for the facile incorporation of aminoalkyl groups into the aromatic ring. This reaction has a great scope of forming aza-stereocenters which can be tuned by different asymmetric catalysts. This review assembles recent advances in asymmetric aza-Friedel–Crafts reactions mediated by organocatalysts. The mechanistic interpretation with the origin of stereoselectivity is also explained.
Keywords: asymmetric; aza-Friedel–Crafts reaction; H-bonding; organocatalysis; stereoselectivity